Applying the RE-AIM conceptual framework for the promotion of physical activity in low- and middle-income countries - Rebecca E. Lee; Karla I. Galavíz; Erica G. Soltero; Jose Rosales Chavez; Edtna Jauregui; Lucie Lévesque; Luis Ortiz Hernández; Juan Lopez y Taylor; Paul A. Estabrooks (Revista Latino-Americana de Enfermagem, 2017)
ABSTRACT Objective: the RE-AIM framework has been widely used to evaluate internal and external validity of interventions aimed to promote physical activity, helping to provide comprehensive evaluation of the reach, efficacy, adoption, implementation and maintenance of research and programming. Despite this progress, the RE-AIM framework has not been used widely in Latin America. The purpose of this manuscript is to describe the RE-AIM framework, the process and materials developed for a one-day workshop in Guadalajara, and the acceptability and satisfaction of participants that attended the workshop. Methods: lecture, interactive examples and an agenda were developed for a one-day RE-AIM workshop over a three month period. Results: thirty two health care practitioners (M age = 30.6, SD=9.9 years) attended the workshop. Most (100%) rated the workshop as credible, useful (100%) and intended to apply it in current or future research (95%). Conclusion: results suggest intuitive appeal of the RE-AIM framework, and provide a strategy for introducing the utility and practical application of the framework in practice settings in Mexico and Latin America.